Constructing Metropolitan Imaginaries: Who Does This and Why? - Feiertag, Patricia; Harrison, John; Fedeli, Valeria (Springer, 2020)
A growing variety of actors has been producing imaginaries of metropolitan regions corresponding to their interests. The cast has been opened up from planners, academics, and local–regional–national state actors to international actors, think tanks, and management consultancies, leading to a greater variety of sometimes short-lived, competing imaginaries. The chapter aims to interrogate the motivations of the social actors actively involved in constructing the vision(s) over time. We use various examples of the European Union, German national spatial visions, Atlantic Gateway in the UK, the megaregions concept, and an expert competition the metropolitan region of Helsinki. We argue that creating spatial imaginaries is not a primary realm for planners, thus on the one hand less transported by plans or even cartographic representations of a metropolitan region and on the other hand less comprehensive as some of them follow a single purpose such as justifying infrastructure investment.
Keywords: Metropolregion; Regionale Identität; Akteur; Interessenlage; Raumvorstellung; Zukunftsvision; Raumentwicklung; Wachstumsmodell; Bedeutungsverlust